Experimental Investigation on mechanical properties of Al6061 Hybrid Metal Matrix Composite Reinforced with Silicon Carbide and Graphite - Nandakumar, N (International Journal of Computer Sciences and Engineering, 2025)
Aluminium (Al6061) possesses excellent Castability and considered as the prominent materials widely used for various mechanical applications. Lower mechanical properties such as strength, hardness and wear resistance of the Aluminium alloy is major limitation for their use in many areas. Their limitation can be prevailed by producing hybrid metal matrix aluminium composites with appropriate selection of reinforcement material and process. In this present experimental work, Graphite is chosen as reinforcement material owing to its exceptional wear and heat resistant properties and the other reinforcement material Silicon Carbide - for its Hardness, tensile strength and enhancing yield strength characteristics. The reinforcement materials were added and by stir-casting method the cast components were produced and are subjected to various tests to find their improved Properties. Wear test was carried out using pin-on-disk wear testing machine and the microstructure analysis was studied on an Inverted optical metallurgical microscope at a magnification factor of 200X. The values obtained from the test result shows that Al6061 alloy hybrid metal matrix composite processed with addition of different weight percentage of reinforcement particles Silicon Carbide (SiC) and Graphite (Gr) in volume percentage combinations resulted in the significant improvement in mechanical properties.